KAJIAN BENTUK DAN FUNGSI MOTIF BATIK MAGELANGAN DI RUMAH INDUSTRI IWING BATIK KEBONPOLO KOTA MAGELANG - Aldona, Faradila; Pratiwinindya, Ratih Ayu (Eduarts: Jurnal Pendidikan Seni, 2024)
The city of Magelang, as an area that does not have a cultural background in batik, is now developing both in terms of form and function with a diversity of motifs due to the influence of Yogyakarta, Solo and Pekalongan Batik to have batik products and motifs that follow the times (trends) with characteristics that are closely related to Magelang City. The visual beauty value of Magelang Batik was created from the idea of the potential advantages of various regions and then visualized in the form of batik motifs and colors as an effort to develop regional batik identity which is felt to be less widespread, so it needs to be of concern to the local community to be aware of the value of local cultural wisdom and understand more along with returning people's interest in batik artwork. The problems studied in this research are: (1) the form of Magelangan Batik motifs in the Iwing Batik Kebonpolo industrial house, and (2) the function of Magelangan Batik in the Iwing Batik Kebonpolo industrial house. The research location is in the Iwing Batik Kebonpolo industrial house which is located at Gg. Arum, Wates Tengah, RT.1/RW.2, Wates Village, North Magelang District, Magelang City, Central Java. This research uses descriptive qualitative research methods. Data collection techniques use observation, interviews and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and verification/drawing conclusions. The results of the research show that several Magelang Batik motifs, including two-dimensional works of art, include geometric and organic shapes with a diversity of motif shapes, colors, arrangement patterns, and repetitive rhythms, which are able to create the impression of a balanced composition with its own charm, thus forming a unity in Magelang Batik. . Magelang Batik also has (1) a personal function as a means of communication, expressing oneself through ideas. (2) The social function provides a collective influence as a means of education, entertainment and appreciation to attract public interest, as well as to meet economic needs. (3) Practical physical functions in the form of clothing, fashion accessories, accessories and souvenirs (merchandise). The existence of Magelang Batik has experienced development in line with changes in the lifestyle of the surrounding community which continues to try to meet living needs and market interests which also continue to grow.